Білорусько-українські етнокультурні взаємовпливи на просторі гомельсько-чернігівського пограниччя (за матеріалами поховальної обрядовості) - Боряк, О. (Матеріали до української етнології, 2014)
На прикладі поховально-поминального комплексу обрядів розглянуто соціокультурний вміст простору українсько-білоруського пограниччя в межах півдня Гомельської області Білорусі (у порівнянні з фактографічним матеріалом, зібраним на півночі Чернігівської області України). Наголошується, що ця етноконтактна зона є перехідною і відкритою для крос-культурних взаємодій і процесів взаємозбагачення при збереженні нею певних локальних рис. На примере погребально-поминального комплекса обрядов рассматривается социокультурная составляющая простора украинско-белорусского пограничья в пределах юга Гомельской области Беларуси (в сравнении с фактографическим материалом, собранным на севере Черниговской области Украины). Акцентируется внимание, что данная этнокультурная зона является переходной и открытой для крос-культурных взаимодействий и процессов взаимообогащения культур при сохранении её локальных черт. The research on the areas of common living of communities of various nationalities can help us to solve theoretical and practical problems as well. For comparative analysis of burial-funeral rites, we have selected administrative regions of Byelorussia (Homelskyi, Lojevskyi, Rechytskyi districts of Homel oblast) bordering on Ukraine (Chernihiv region). Accordingly, only a few separate elements of ritual practice are outlined in the area of the administrative border between the two states. At the same time, this area is a rather wide ethnocultural transfer space, where specific historical and cultural processes take place. This is the territory where cross-cultural interrelations and multiple-layer cultural ties can be visibly seen. Main components of the subject and actional row of the burial-funeral complex indicate this. This is a unique space where events of culture, first of all, spiritual, not only constantly interrelate and mutually enrich one another, but also synthesize themselves, keeping separate elements of “differences”.